The role of urban green space in promoting sustainable development: a study on Putrajaya, Malaysia - Mohd Nor, Nurfarhana; Sahrir, Syazwani (Malaysian Institute of Planners, 2024)
Urban Green Spaces (UGS) contribute to sustainable development, a key goal for every country, encompassing social, economic, and environmental aspects. This study involves two objectives: to identify the elements of UGS that contribute to sustainable development and to explore the role of UGS in contributing to sustainable development. A qualitative research design was chosen to achieve these objectives using document analysis (from official reports, journals, and analyses) and semi-structured interviews. The study's findings show that UGS plays a role in contributing to sustainable development involving environmental, social, and economic dimensions, explained through data triangulation. The elements of UGS identified include buffer zones, conservation green spaces, recreational/community green spaces, amenity green spaces, greenways, building greens, agricultural land, and blue areas. Additionally, the roles of UGS in environmental aspects include air quality benefits, water quality benefits, ecological functions, and support for local nature; in social aspects, they enhance interpersonal relationships, recreational activities, human health, human wellbeing, educational functions, and overall quality of life; in economic aspects, they contribute to market values. UGS is a crucial component of sustainable urban planning, essential for fostering cities that are both sustainable and resilient. Its multifaceted contributions to environmental health, social interaction, and economic vitality highlight its indispensable role in creating healthier, happier, and more resilient urban environments.